Hubungan Lama Penggunaan Kontrasepsi Suntik Dmpa Dengan Kenaikan Tekanan Darah Di Puskesmas Baruga Kabupaten Bantaeng Tahun 2023 - Dewi, Dewi; Ernawati, Ernawati; Sumarmi, Sumarmi; Nuryana, Riska (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
The contraceptive injection is one of the highly effective, safe, convenient, and reversible forms of contraception, but it can lead to irregular menstruation, increased blood pressure, depression, vaginal discharge, acne, changes in weight, and hematomas. The aims of this research is to examine the correlation between the use of DMPA contraception and the increase in blood pressure at Baruga Health Center in 2023. This research method utilizes an observational cross-sectional study and employs Accidental sampling technique for sample collection. This analytical study uses Chi-Square Test analysis. The research results show that the chi-square test analysis was p=0.05, so it can be interpreted that there is a relationship between the use of DMPA injections and an increase in blood pressure.